EKSPLORASI LUMUT HATI (Marchantiophyta) PADA GENUS Cyathodium DI KEBUN RAYA CIBODAS - Rahmadani, Gita Suci; Triastinurmiatiningsih, .; Nadhifah, Ainun (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2023)
Bryophyte is classified as a plant in which its parts cannot be distinguished (thallus), bryophytes can grow on various substrates, such as on bark (epiphytes), rocks, wood, and can grow on the surface of the soil (terrestrial). One of the locations in West Java that has the potential for moss diversity is the Cibodas Botanical Gardens. One of which is a type of liverwort from the genus Cyathodium. resembles a fan and splits into two Cyathodium has a bright green color, and has a pungent odor. Cyathodium is commonly found around the waterfall area, due to the natural environment, humidity, and abundant water. This study aims to determine the diversity of the genus Cyathodium that grows in the Cibodas Botanical Gardens and to determine the morphological and anatomical characteristics of the genus Cyathodium. This research was conducted from March to May 2022. The research location is in the tourist area of Ciismun Waterfall, Cibogo Waterfall, and in office cliff Cibodas, Cianjur Regenc, West Java. The method used is descriptive research method with a qualitative approach. Identification is done using an identification key. The results of the study found 1 type of liverwort from the genus Cyathodium, namely the type cyathodium foetidissimum Schiffn. Survival, and abundance The diversity of moss species is strongly influenced by appropriate environmental factors, these environmental factors are abiotic factors and biotic factors, while abiotic factors include temperature, humidity, soil pH and altitude, while biotic factors include plants in the area.